Transradial versus transfemoral artery access in mechanical thrombectomy for acute ischemic stroke: An updated systematic review and meta-analysis - Amjad Almansi (17738179) (2024)
Introduction Recently, transradial access (TRA) for mechanical thrombectomy in acute ischemic stroke has been proposed as an alternative due to potential advantages such as reduced access site complications. However, its safety and efficacy compared to the traditional transfemoral access (TFA) remain debated. Methods We conducted a comprehensive search on PubMed, Scopus, Web of Science, Cochrane Library, and Embase from inception to May 15, 2024. We included all randomized controlled trials and observational studies. The primary outcome was successful recanalization, defined as achieving Thrombolysis in Cerebral Infarction (TICI) grades 2b–3. Secondary outcomes included complete recanalization (TICI grade 3), achieving TICI 2c or higher, functional outcomes (modified Rankin Score (mRS) at discharge and 90 days, mRS 0–2 at 90 days, National Institutes of Health Stroke Scale (NIHSS) at discharge, Length of hospital stay (LOS)), procedural efficiency (access-to-perfusion time, first-pass reperfusion, mean number of passes, crossover to alternate approach), and safety/survival outcomes (access site complications, symptomatic intracranial hemorrhage, in-hospital and 90-day mortality). This study was registered in PROSPERO (CRD42023462293). Results The meta-analysis included 13 studies with a combined total of 4759 patients. No statistically significant difference was found between TRA and TFA for successful recanalization (RR = 1.00 [95 % CI, 0.97–1.04], P = 0.88). Analysis also showed no significant difference in favorable functional outcomes between groups (RR = 0.88, [95 % CI, 0.71–1.09], P = 0.25) with significant heterogeneity (P = 0.008, I² = 71 %), which was resolved by excluding the study of Phillips et al., 2020 (P = 0.58, I² = 0 %), then favoring TFA over TRA (RR = 0.80, [95 % CI, 0.70–0.92], P = 0.002). TFA also had a statistically significant lower risk of crossover to TRA (RR = 1.68, [95 % CI, 0.99–2.86], P = 0.05). Overall, TRA was associated with a significantly shorter length of stay (MD = −1.49, 95 % CI [-2.93 to −0.05], P = 0.04, I² = 75 %), though sensitivity analysis showed a non-significant mean difference still favoring TRA (MD = −0.59; 95 % CI: [-1.28 to −0.10], P = 0.09, I² = 0 %). There was no difference between TRA and TFA regarding complete recanalization, achieving TICI 2c or higher, procedural efficiency, functional outcomes, safety, and survival. Conclusion Our updated meta-analysis demonstrates that TRA is comparable to TFA, except for a higher proportion of patients achieving mRS 0–2 at 90 days with TFA, lower crossover rates with TFA, and possibly a shorter length of stay (LOS) with TRA. Further research, particularly randomized studies, is needed to confirm these findings due to the observational nature of included studies. Other Information Published in: Clinical Neurology and Neurosurgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clineuro.2024.108585